Pengembangan Sistem Penagihan Biaya Kuliah Dengan Fitur WhatsApp Menggunakan Metode Scrum Berbasis Website - Eko Setiadana (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
The development of information technology today allows various applications to communicate with each other. One of the emerging technologies is Web Service. Web Service resolves as a software system designed to support interoperability of machine-to-machine interaction over a network. The main focus of this research is to develop a tuition fee billing system using the Scrum method to make the process of billing tuition fees simpler, so a website-based system is developed with the Whats App feature to send tuition billing notifications to students. Making this application is supported by several technologies such as Sublime Text, MySQL and WhatsApp